Growth and Issues of Small and Medium Enterprises in Post conflict Jaffna Sri Lanka - Vijayakumar, S. (CORE, 2013)
The growth and development of SMEs in Jaffna is vulnerable due to the three decades of internal war. Even having finished the war, there is no remarkable progress in the development of SMEs in Jaffna. Thus, main objective of study is to scrutinize the severity and degree of issues of small and medium enterprises in post conflict Jaffna. The second objective is to identify the growth status of SMEs in Jaffna. Self administered Likert scale questionnaire has been employed for the analysis of study. The results bring to light the fact that mean value of assets , value of turnover and mean value of number of employees as well as growth stages of SMEs clearly show that there is very poor growth of small enterprises in Jaffna. Another finding is that the mean values of all issues of SMEs are closer to one or two indicating that small enterprises of Jaffna have been undergoing several severe problems in the growth of business in post war. Government should give more priority in policy making to the development of SMEs of North and East where as political and economic climate should be conducive to flow foreign and local investment into North and East region. This is a first empirical study in regard to SMEs after 30 years civil War in the region. This study will be giving new insights to the policy makers and government. In addition, those who are interested in developing their business in the same region can acquire valuable information and knowledge about SMEs.
Keywords: growth; Northern Province; political climate; post civil war; small and medium enterprises